Comparing the clinical and prognostic impact of proximal versus nonproximal lesions in dominant right coronary artery ST‐elevation myocardial infarction. Issue 5 (1st September 2020) - Femia, Giuseppe; Faour, Amir; Assad, Joseph; Sharma, Lokesh; Idris, Hanan; Gibbs, Oliver; Pender, Patrick; Leung, Dominic; Hopkins, Andrew; Rajaratnam, Rohan; P Juergens, Craig; Mussap, Christian; et al.
Abstract: Objective: To evaluate the prognostic significance of culprit lesion location in dominant right coronary artery (RCA) ST‐elevation myocardial infarction (STEMI). Background: In RCA STEMI, proximal culprit lesions have been shown to have higher rates of acute complications such as bradycardia and cardiogenic shock (CS) but data on mortality is limited. Methods: We retrospectively identified and analyzed data from consecutive patients with a dominant RCA STEMI who underwent either primary or rescue percutaneous coronary intervention (PCI) between January 2003 and December 2016. We compared the rates of sustained ventricular tachycardia (VT), CS, intra‐aortic balloon pump (IABP), temporary cardiac pacing (TCP) and death between culprit lesions located proximal and distal to the origin of the last right ventricular (RV) marginal artery >1 mm in diameter. Results: The 939 patients were included; 599 (63.7%) had a proximal lesion and 340 (36.3%) had a nonproximal lesion. The 801 (85.3%) underwent primary PCI and 138 (14.7%) underwent rescue PCI. There was no difference in first medical contact to balloon or fibrinolysis times between the groups; p = .98 and .71. There was no significant difference in the rate of sustained VT (3.0%vs. 3.2%, p = .85) but proximal lesions were more likely to develop CS (10.9%vs. 5.8%, p = .01), require IABP (7.3%vs.2.9%, p < .01) and TCP (6.3%vs. 2.6%, p = .01). Thirty‐day mortality was higher for proximal lesions (5.0%vs. 0.9%, p < .01) particularly for those with CS (35.3%vs. 10.0%, p = .05). Conclusion: Culprit lesions located proximal to the origin of the last RV marginal artery had a higher rate of acute complications such as CS and mortality.